Technical construction tools in a novel "The Dream of Long Distance" by Suleiman Al Qawabba - El- Shishiny, Osama Mohamed (Arab Journal for Sciences and Research Publishing, 2020)
This research promotes the acquaintance with a writer from the writers distinguished in the creativity of the narrative text، through criticizing his novel The Dream of Distant Distances، and the two visions: substance and constructivism will be highlighted.The research presents the indications that the writer intended for his creativity، whether these indications are social or political، relying in this on a concerted artistic construction in which the vocabulary of the narrative text is concerned، the relationship of the form to the content، because whatever the contents and ideas that the literary text holds، they are of little benefit، or not Influential at best، unless it is embodied in an expressive and attractive artistic style، through which the writer can reach the achievement of a text in which the content with the form is a coherent organic unity.
Keywords: Artistic Structure; The Novel; A Dream of Distant Distances; Sulaiman Al-Qawabah